DYNAMICS OF ENVIRONMENTAL FACTORS AND REALIZATION OF THE POTENTIAL PRODUCTIVITY OF ECOSYSTEMS WITH MEADOW-CHESTNUT SOILS IN THE TEREK-KUMA PERI-CASPIAN LOWLAND - G. N. Gasanov (Ûg Rossii: Èkologiâ, Razvitie, 2015)
The aim is to reveal theoretically possible productivity of pasture phytocenosis on meadow-chestnut soils in protected area of Terek-Kuma Lowland.Methods. To determine the dynamics of the basic physical and chemical properties of soil, evaporation, humidity coefficient (HC) of the area, the productivity of phytocenoses and utilization factors of photosynthetically active radiation (PAR).Results. Highly productive ephemeral synusia (5 q/ha of air-dry weight) is formed in years with precipitation of 80-85 mm during April - May at a relative humidity of 70-73%, with evaporation of 130-140 mm, humidity coefficient of 0.30, and integral of moisture of 29.8. Decreasing precipitation amount in the same period to 25-26 mm, the relative humidity to 61%, humidity coefficient to 0.06, evaporation to 200-202mm form an integral of aridity of 37.3, where the 0- 24 cm Cl ion content in the soil increase to 5.56 mgEq/100g, the yield of a biomass is reduced to 1.0 q/ha. Increase of 102 mm in rainfall in July – August period results in humidity coefficient increase - 0.21, decrease of Cl- content in horizons of А+В to 1.40 mg-eq./100g. Productivity of grasses and saltwort increases to 21.1q/ha. The utilization factor of PAR by phytocenosis makes up 0,023-0,033 (21.4% share of ephemera, herbs and saltwort make up 78.6%) and had little effect on productivity of phytocenosis.Main conclusion. The formation of a biomass in the meadow-chestnut soil is the result of the combined effects of the amount of rainfall, evaporation, humidity coefficient, the degree and the chemistry of soil salinity. Were calculated multiple regression equations expressing the relationship between these factors.